(untitled) (Palíndromo, 2021)
What you see here is a clipping of an artist’s notebook, which is part the result of a research doctorate in visual poetics of the Postgraduate Program in Visual Arts at the Federal University of Pará, where they are held experiments were carried out between literature and the visual arts, having as this space, a space of fruition, creation and invention. K. is a character, who is a traveling artist, where his story is told through images, words and other artistic processes. It is an invented territory where there is a crossing of borders between languages.